(untitled) (Journal of Applied Engineering Science, 2024)
CLARIFICATION The author’s name Dessy Angga Afriyanti was misprinted within the article in subject published in 22(2024)1, 1181, 223-233, DOI:10.5937/jaes0-45719. Authors’ name should be corrected as follows: Dessy Angga Afrianti This addition does not affect the original paper. We apologize for any inconvenience that this may have caused.